Acute viral hepatitis – Should the current screening strategy be modified? - Harvala, Heli; Wong, Vincent; Simmonds, Peter; Johannessen, Ingolfur; Ramalingam, Sandeep (Journal of clinical virology, 2014)
The epidemiology of viral hepatitis has changed. Since the introduction of safe and effective vaccines for hepatitis A and B in 1980s, the incidence of acute infections caused by these viruses has been declining in the UK. At the same time, hepatitis E virus (HEV) has been recognised as an increasingly important cause of acute hepatitis, but testing is not widely available. The aim of this study was to establish the viral causes of acute hepatitis, and use that data to modify the current diagnostic algorithm. A Cognos search was performed to collate subjects tested for HAV, HBV, HCV, HEV, EBV and CMV between June 2010 and December 2012. Information included virological result and their ALT level if done within 5 days from virological testing. From 3462 subjects with suspected acute viral hepatitis, only 25% had biochemical evidence of acute hepatitis (n=854; ALT>100IU/l). The frequency of detection of acute HEV infection (25/409) was over 31-times higher than that of HAV (6/3462), and 7-times higher than that of HBV (24/3462). Most cases of acute HAV, HEV, EBV and CMV infections presented with abnormal ALT levels. Most EBV infections were associated with lymphadenopathy (23/34); in comparison most of CMV infections were not associated with lymphadenopathy (18/22). HEV screening should be included in the initial testing panel for acute hepatitis and screening at least for HAV and HEV might be limited to those with abnormal ALT levels.